Desertification in semi-arid northeast of Brazil | Desertificação no nordeste semi-árido do Brasil - Costa, Amanda Rodrigues Santos; Ferreira, Gleide de Lima; de Souza, Elizabete Buonora; Rolim Neto, Fernando Cartaxo (Revista Geama, 2016)
Desertification is the process of land degradation in arid, semi-arid and dry sub-humid areas, caused, among other factors, by human activities and climatic variations. It is a global-scale problem because it is present in the dry regions in the world and causes many losses. In Latin America alone, over 516 million hectares are affected by desertification. As a result of this process are lost 24 billion tons per year of topsoil, affecting the economic, social and environmental development. In Brazil, the most likely region to this process is the northeastern semi-arid region, where the Caatinga biome occurs, due to the dry climate of the area and human activities for the exploitation of natural resources and agricultural practices without proper management for soil conservation. As aggravating the situation there is the scenario of climate change that can alter the rainfall patterns in the region and the climate in general, increasing the desertification process. To prevent and combat this process, are used legal instruments and government programs that seek to provide guidelines for action and implement preventive and recovery practices in degraded and susceptible to desertification areas. The scientific community is also active in tackling the problem with studies and research aimed at discussion of the topic.